Lack of Effects of Renin-Angiotensin-Aldosterone System Activity and Beta-Adrenoceptor Pathway Polymorphisms on the Response to Bisoprolol in Hypertension - Zeng, Weiwei; Chu, Tanya T. W.; Ho, Chung Shun; Lo, Clara W. S.; Chan, Alan S. L.; Kong, Alice P. S.; Tomlinson, Brian; Chan, Sze Wa (Frontiers in Cardiovascular Medicine, 2022)
Purpose: This study examined the effects of plasma renin activity (PRA), angiotensin II (Ang II) and aldosterone (PAC) concentrations as well as common polymorphisms in the β1-adrenoceptor gene (ADRB1) and the G-protein α-subunit (Gαs) protein gene (GNAS) on the blood pressure (BP) and heart rate (HR) response to bisoprolol in Chinese patients with hypertension. Methods: Patients with sitting clinic systolic BP (SBP) 140-169 mmHg and/or diastolic BP (DBP) 90-109 mmHg after placebo run-in were treated with open-label bisoprolol 2.5 mg daily for 6 weeks. Patients diagnosed as having primary aldosteronism or renal artery stenosis were excluded. PRA, Ang II and PAC concentrations were measured after the placebo run-in and after 6 weeks of treatment. The Ser49Gly and Arg389Gly polymorphisms in ADRB1 and the c.393C>T polymorphism in GNAS were genotyped by the TaqMan® assay. Results: In 99 patients who completed the study, baseline PAC levels were significantly associated with baseline DBP and plasma potassium on univariate but not on multivariate linear regression analysis. PRA, Ang II and PAC concentrations at baseline were not associated with changes in BP with bisoprolol treatment, but the values were all significantly reduced (PRA -0.141 ± 0.595 ng/mL/h, Ang II -2.390 ± 5.171 pmol/L and aldosterone -51.86 ± 119.1 pg/mL; all P<0.05) following 6 weeks of bisoprolol treatment. There were no significant differences in BP or HR responses in patients with baseline PRA above or below the PRA cut-point of 0.65 ng/mL/h or the median value of 0.9 ( ng/ml/hour. There were no significant associations of the ADRB1 and GNAS polymorphisms with the clinic and ambulatory BP and HR responses to bisoprolol.Conclusion: Baseline PRA, PAC and Ang II concentrations showed no significant association with the the BP response to bisoprolol treatment, but all these parameters were reduced after 6 weeks of treatment with bisoprolol. The two common polymorphisms in ADRB1 and the c.393C>T polymorphism in GNAS had no significant association with the BP and HR response to bisoprolol in these patients.